The Role and Strategy of Aqidah Akhlak Teachers in Instilling Moral Values and Tolerance to Minimize Bullying Among Students at Mts Tri Bhakti At-Taqwa - Asih Azzahra; Irhamudin; Jauharotun Nafisah (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
Bullying is a common problem in schools and can negatively impact students' psychological and social development. Therefore, effective efforts are needed to prevent and minimize bullying behavior among students. One such effort is through the instilling of moral values and tolerance in Akidah Akhlak learning. This study aims to determine the role and strategies of Akidah Akhlak teachers in instilling moral values and tolerance to minimize bullying among students at MTs Tri Bhakti At-Taqwa. This study uses a qualitative approach with field research. Data collection techniques are carried out through observation, interviews, and documentation, while data analysis uses data reduction, data presentation, and conclusion drawing techniques. The results of the study indicate that Akidah Akhlak teachers have an important role in shaping students' character through the instilling of moral values such as mutual respect, respect for differences, and fostering empathy for others. Schools need to strengthen the role of teachers as agents of character formation, integrate moral education consistently into the curriculum, and create a school environment that supports the practice of tolerance so that bullying prevention can take place sustainably and effectively.